Pengaruh Sistem Pengendalian Internal, Moral Sensitivity, Kompetensi Sumber Daya Manusia Terhadap Kecenderungan Kecurangan Pengelolaan Keuangan Badan Usaha Milik Desa - Widiastuti, Ni Komang Ayu Arya; Indraswarawati, Sang Ayu Putu Arie; Yuniasih, Ni Wayan (Hita Akuntansi dan Keuangan, 2024)
Village-Owned Enterprises (BUMDes) are villages efforts to encourages and also accommodating all activity that increasing community income, both those that develop in accordance with local custom and cultures and also economic activities that are handed over to the community through government and regional government program and project. Thisi researchi wasi conductedi toi determining thei influencei ofi the Internali ControliSystemsi, Moral Sensitivity andi Humani Resources Competencei oni thei Tendency of Fraudulent Financial Management of Village-Owned Enterprises in Klungkung Regency. The populations in this research is Village-Owned Enterprises in the savings and also loans sector in Klungkung Regency. The number of sample in this study was 95 peoples, determine using a saturated sample technique and tested use multiple linear regression analysis technique. The result of this research indicating that the Internal Control System, Moral Sensitivity and also Human Resource Competence have a negative effects on the Tendency of Fraud in the Financial Management of BUMDes.